Iowa RBA, September 28, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for September 28, 1998. Highlights include Red-shouldered Hawk, Yellow Rails, and Eurasian Collared Doves. Includes notes for updates for October 1. Epson - sheet feed/flatbed